MAYA INDEX DAN KEPADATAN LARVA AEDES AEGYPTI ANTARA DUSUN TEGALREJO DAN DUSUN KRAJAN KIDUL NANGGUNGAN PACITAN - Yelly Atiefsa Narmala; R. Azizah (The Indonesian Journal of Public Health, 2019)
Dengue fever remains a public health problem. Environmental factors influence the mosquito Aedes aegypti’s growth, especially if there are many containers in the neighborhood. The community of Nanggungan Village have a habit of storing water in containers, therefore, they risk to become breeding sites for mosquitoes. This study aims to identify the Maya Index status of Aedes aegypti between Tegalrejo and Krajan Kidul Village. The research was observational with a cross-sectional design. Total samples were 200 homes, which 100 homes from Tegalrejo and 100 homes from Krajan Kidul Village, taken by simple random sampling. The measurement of variables employed observation sheet and analyzed in a descriptive approach. The number of containers observed in the Tegalrejo Village was 394 units, and Karajan Kidul Village was 391 units. Maya Index statuses in Tegalrejo (92%) and Krajan Kidul Village (88%) were low. Maya Index status in Krajan Kidul (13%) was higher than Tegalrejo Village (8%). House Index (HI) in the Tegalrejo (18.0%) was lower than Krajan Kidul Village (25.0%), Container Index in Tegalrejo (5.30%) was lower than in Krajan Kidul Village (8.95%), Breteau Index in Tegalrejo (21.0%) was lower than in Krajan Kidul Village (35.0%), Density Figure in Tegalrejo and Krajan Kidul Village indicated a scale of 3 and 4. Based on the MI’s status, Tegalrejo and Krajan Kidul Village were included as a low-risk category of mosquito breeding sites. Based on the density number of larvae, two villages have a moderate risk of Dengue Fever transmission. The community should implement the Mosquitoes Breeding Sites Eradication Program (PSN 3M Plus) and minimize the presence of the containers.